Detection and Analysis of Common Substances Used in Drug-Facilitated Sexual Assault (DFSA). A Forensic Laboratory-Based Study - Fariha Tariq, Iffat Imtiaz Iffi, Kishwar Naheed, Farhat Sultana, Khalid Mahmood (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Drug-Facilitated Sexual Assault (DFSA) is a form of sexual violence in which perpetrators administer psychoactive substances to incapacitate victims, impairing memory and resistance. Rapid detection of these agents is essential for effective medico-legal investigation and prosecution. Objective: To detect and analyze the most common substances implicated in DFSA cases in Lahore, Pakistan, using complementary analytical methods. Methods: A cross-sectional descriptive study was conducted at the Forensic Medicine Departments of King Edward Medical University and Services Institute of Medical Sciences, Lahore, from January 2022 to January 2023. Fifty suspected DFSA cases referred for medico-legal examination were included. Biological specimens (blood, urine, hair) were collected following chain-of-custody protocols and analyzed using Gas Chromatography-Mass Spectrometry (GC-MS) and Liquid Chromatography–Tandem Mass Spectrometry (LC-MS/MS). Data were analyzed using descriptive statistics. Results: Out of 50 cases, 37 (74%) tested positive for at least one incapacitating agent. Benzodiazepines were the most frequently detected (43.2%), followed by ethanol (29.7%), gamma-hydroxybutyrate (16.2%), ketamine (8.1%), and sedating antihistamines (2.7%). Polydrug use was observed in 21.6% of positive cases. Urine was the most productive matrix (75.7% positivity), followed by blood (51.4%) and hair (8.1%). GC-MS was particularly effective for volatile and semi-volatile compounds, while LC-MS/MS demonstrated superior sensitivity for low-dose and short-half-life drugs. Conclusion: Benzodiazepines, ethanol, and GHB were the predominant DFSA agents in this series. A combined GC-MS and LC-MS/MS approach significantly enhanced detection rates, especially in polydrug cases. Early reporting, multi-matrix collection, and advanced analytical techniques are critical for improving toxicological confirmation in DFSA investigations. Keywords: Drug-Facilitated Sexual Assault, Forensic Toxicology, Benzodiazepines, GHB, GC-MS, LC-MS/MS.